2016
DOI: 10.1515/bnm-2015-0019
|View full text |Cite
|
Sign up to set email alerts
|

Towards microstructure-cytocompatibility relationship in ultralight Mg-4Li-1Ca (LX41) alloy for degradable implant applications

Abstract: Cytocompatibility and biodegradation behaviour were investigated for a newly developed ultralight Mg-4Li-1Ca (LX41) alloy with different starting microstructures. This established the important role of microstructure in determining the pH variation, H 2 evolution and amount of ions (Mg, Li, Ca) released during degradation. Thus, different thermomechanical treatments were utilised to alter the microstructure of the alloy and to evaluate its bio-response. The as-cast and two step rolled+annealed (TA30) materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…As for Mg-4 wt.% Li-1 wt.% Ca (LX41) alloys, Nene et al [ 28 ] designated an as-rolled LX41 alloy with significant improvement in mechanical properties with an ultimate tensile strength (UTS) of 250 MPa. Moreover, Sommer et al [ 29 ] conducted in vivo LX41 tests and suggested that LX41 possesses good osseointegration and new bone formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for Mg-4 wt.% Li-1 wt.% Ca (LX41) alloys, Nene et al [ 28 ] designated an as-rolled LX41 alloy with significant improvement in mechanical properties with an ultimate tensile strength (UTS) of 250 MPa. Moreover, Sommer et al [ 29 ] conducted in vivo LX41 tests and suggested that LX41 possesses good osseointegration and new bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…For the human body, the normal blood serum level of Li is 2–4 ng/g [ 31 ]. The Li level in Earle's balanced salt solution can be influenced by the microstructure (grain size and secondary phases) of LX41 alloy [ 32 ]. To our best knowledge, the release rate of dissolved ions during degradation with time has sparsely been reported so far.…”
Section: Introductionmentioning
confidence: 99%